(untitled) (Revista Electrónica REDINE, 2018)
This article presents a breakthrough in development research, which aims to generate a theoretical approach on the holocompetency metameaning in university management. Qualitative research is supported in such epistemic phenomenological hermeneutical approach, through in-depth interviews conducted with actors or key informants. It is intended to show a manager with holistic and integrated thinking mode , manager of his own future, the university, the community and society; facilitator of human development, culture of being, welfare, the awakening of consciousness to transcendental and universal values.